Calcified Abdominal aortic occlusion: Treatment using Intravascular Lithotripsy - Shah, Pratik; Someshwar, Vimal; Mundada, Krishna; Raut, Abhijit (Journal of Clinical Interventional Radiology ISVIR, 2022)
Near total occlusion of abdominal aorta due to atherosclerotic calcification is a challenging condition to treat. Though use of intravascular lithotripsy (IVL) has proven to be an effective technique in the treatment of calcified arterial lesions, the data on the use of the technique in high grade occlusion of aortic stenosis is still limited. We present a case of abdominal aortic calcification treatment in a patient using IVL technique.
Keywords: abdominal aortic calcification; IVL technique; IVUS